Role of Mangrovian Biodiversity, Ecological Distribution and Abundance, for Promising Sea Reclamation: A Case Study in Sea West of Kien Giang Province - Luom Thanh Thai; Anh Tuan Nguyen; Bao Manh Ngoc Nguyen; Hao Thanh Truong; Anh Quynh Le (Geography, Earth Science and Environment: Research Highlights Vol. 4, 2025)
Purpose: The purpose of this study is to help readers understand the important role of mangrove forests in biodiversity and their development, which is very useful for present and future people if they know how to protect and develop them. Background: If the tree species are not protected, some species may become extinct due to land expansion for residential development and agricultural and fishery production. So, it is necessary to investigate and discover tree species abundant in the Mekong Delta in order to develop land on the southern coast of Vietnam and based on that apply for food and medicine of forest trees. Western Mekong Delta (WMD) had alluvium sediments flow from upstream China to Vietnam by the river branches, then get out the sea. These sediments accumulated gradually with the elevation of the new land. The coastal where mangrove forests with a rich ecosystem of plants and animals. Over time, these forests change, with different plant species succeeding each other. This study aims to find plant species, forest types based on ecological regions, biodiversity of tree species, and abundance communities, measured growth of the forest in this region. Methods: In 2023, a comprehensive survey was conducted using a systematic approach. Ecological zoning was done based on soil distribution, topography, water regime and plant community distribution, and divides the ecological areas that variety of characteristics into different ecological sub-regions. Investigate the situation of woody plant species in mangrove forests in sub-regions. The number of survey plots depends on the density of the forest. Based on the width of the forest range, the number of survey plots in the sub-region is set up from 10 to 15 plots. In total, 68 plots have been established in this area, the area of the plot is 100 square meters (10m x 10m). The statistical software was used to survey and analyse data. PRIMER 6 software was used to analyze similarities between species. Results: Based on the soil properties, topography, and distribution of mangrove forest vegetation in the western sea of the Mekong Delta, the mangrove forests in this region are divided into 4 sub-regions. Found the number of species in each ecological region and growth situation, in which the important thing is to evaluate the adaptation of species in each sub-region to propose which species to choose as the main species in afforestation the fastest land on the sea. The result provided a picture of the tree species composition, distribution, and community structures in each sub-region. The result of the survey showed that sub-region one has seven species; sub-region two has eleven species; sub-region three has eight species; and sub-region four has ten species. Of the total species of the mangrove forest in the Western Mekong Delta 16 species from 11 plant families have been identified. Among these species, 6 dominant species Avicennia officinali), Avicennia alba, Rhizophora apiculata, Excoecaria agallocha, Someratia caseolaris, and Bruguiera yipamoriza. From the investigation have been found two species that grow best on new land Avicennia officinalis and Avicennia alba these findings show they can develop on the original new land for the shore of the Western Mekong Delta. The survey results also calculated the average height (Ht), diameter (D1.3), canopy (Dc), and health (He) of the natural mangrove tree for each sub-region and total region. Results of the division of forestry structure, the structure of height (H), diameter (D1.3), canopy, and heath (He). Conclusion and Suggestions: The references of Avicennia officinalis, Avicennia alba, Sonneratia caceolaris, Sonneratia ovate, Rhizophora apiculata and other species from leaves and fruits can be used partly to replace starch for food processing livestock and poultry feed and raising aquatic species from renewable bioenergy on mangroves is huge. Based on the current state of the forest to the four current sub-regional conditions, the state builds a sustainable development strategy and mobilizes the community to participate in protecting and developing forests to the natural regeneration conditions of them. There are Avicennia officinalis and Avicennia alba two species that can develop plants to expand natural land by planting a forest. These adapted species can exploit food and medicinal herbs in the biodiversity distribution abundance of these species. It can help Vietnam by measures using the species Aviecennia to be discovered will promote sea reclamation faster instead of letting the natural law of sea reclamation follow.